The Alexander romance by Ps.-Callisthenes : a historical commentary - Nawotka, Krzysztof. (Mnemosyne, Supplements, 2017)
The Alexander Romance by Ps.-Callisthenes of Krzysztof Nawotka is a guide to a third century AD fictional biography of Alexander the Great, the anonymous Historia Alexandri Magni . It is a historical commentary which identifies all names and places in this piece of Greek literature approached as a source for the history of Alexander the Great, from kings, like Nectanebo II of Egypt and Darius III of Persia, to fictional characters. It discusses real and imaginary geography of the Alexander Romance . While dealing with all aspects of Ps.-Callisthenes relevant to Greek history and to Macedonia, its pays particular attention to aspects of ancient history and culture of Babylonia and Egypt and to the multi-layered foundation story of Alexandria.